Effects of freshwater inputs on soil quality in the Yellow River Delta, China. (March 2019) - Zhao, Qingqing; Bai, Junhong; Gao, Yongchao; Zhao, Haixiao; Huang, Yujie; Zhang, Wen; Wang, Jianing; Chen, Guanhong
Highlights: Samples in salt marshes and freshwater restoration wetlands were clearly separated. Higher soil quality index value was observed in salt marshes with Suaeda salsa. Salinity, silt and SOM were key factors influencing soil quality. Abstract: With the degradation or loss of coastal wetlands, more and more restoration projects have been widely conducted. Freshwater inputs have been proved to be an effective restoration way for degraded coastal wetlands. However, little information is available on the changes in soil quality caused by freshwater inputs. Soil samples were collected to a depth of 50 cm in freshwater restoration wetlands (FRW), tidal salt marshes with Suaeda salsa (SSM) and tidal salt marshes with Tamarix chinensis (TSM) in the Yellow River Delta, China, in August 2015, to investigate the changes in soil quality after freshwater inputs. Our results showed that soil salinity was significantly higher in natural wetlands than that in freshwater restoration wetlands (p < 0.05), while no significant differences in soil organic matter (SOM) were observed among three wetlands (p > 0.05). Cluster analysis and principal component analysis exhibited that soil samples in natural wetlands and freshwater restoration wetlands were clearly distinguished. Soil properties were screened and transformed to establish a soil quality index (SQI) for the assessment of soil quality. Soil salinity, SOM and silt were selected in the minimum data set in this study. Although there were no statistical differences in SQIs (p > 0.05), both linear SQI (SQIL ) and non-linear SQI (SQINL ) for three wetlands followed the order: SSM > FRW > TSM. And the SQIL values were lower compared with SQINL . The contributions of soil salinity to SQIL for three wetlands and SQINL for TSM and SSM were the highest in the minimum data for three wetlands, while SOM showed the highest contribution proportion of SQINL for FRW.